Habilidades motoras de crianças e adolescentes praticantes de futebol - Freitas, Raniel Gama (Brasil, 2024)
The objective of this study was to analyze the Motor Skill (HM) of children and adolescents who are beginners in a soccer project. The sample consisted of male children and adolescents aged 11 to 16 years. The instruments used will be: 1) Anamnesis questionnaire; 2) Movement Assessment Battery for Children - Second edition (MABC-2). The design consisted of three steps: 1) Meeting with those responsible for the soccer project of the Physical Education Course at the Institute of Social Sciences, Education and Animal Science of the Federal University of Amazonas (CEF/ICSEZ/UFAM) to request consent to carry out the present research project; 2) Meeting with the legal guardians of the children and adolescents participating in the CEF/ICSEZ/UFAM football project to request authorization by signing the Free and Informed Consent Form (TCLE); 3) Application of MABC2. The result of the present study shows that the individuals in the sample are predominantly brown and of low social class. The Total Standard Score observed is analyzing whether there was an improvement in the development of these HH as they become involved in training frequently and systematically.